Perceptions of racial profiling : Race, religion, and friendship - Puhrmann, Aaron Michael (2006)
There exists a considerable abundance of research focusing on the determinants of attitudes towards police. However, relatively little attention has been paid to the determinants of attitudes towards racial profiling. This thesis seeks to examine the influence of several potential determinants of attitudes towards racial profiling, specifically whether racial profiling is widespread, justified, and personal experience with profiling. The potential determinants of these attitudes include race, religion, and friendship with a member of the police force. The data used in this thesis are from a New York City Police Department Poll conducted in early 2001, which includes 721 New York City residents. Binary logistic regression was used to evaluate the effect of the three hypothesized determinants on attitudes in three separate models. Race was the strongest predictor of such attitudes with significant effects in all three models, while religion and friendship had significant effects in only one of the three models